2010
DOI: 10.1002/pon.1854
|View full text |Cite
|
Sign up to set email alerts
|

Disruption to radiation therapy sessions due to anxiety among patients receiving radiation therapy to the head and neck area can be predicted using patient self‐report measures

Abstract: This study offers some preliminary insights into the prevalence of patient anxiety severe enough to cause session disruption and patient self-report measures which might be used to flag patients for prophylactic treatment. Further development and replication in a larger sample is warranted before introduction of these measures into routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 23 publications
2
78
0
Order By: Relevance
“…Oultram et al and Dong et al also recommended CST to improve detection and management of patient issues including anxiety, claustrophobia, coping and side effects. Clover et al and Oultram et al reported that RTs over‐estimated anxiety compared to patient self‐report, and suggested training may improve accurate detection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oultram et al and Dong et al also recommended CST to improve detection and management of patient issues including anxiety, claustrophobia, coping and side effects. Clover et al and Oultram et al reported that RTs over‐estimated anxiety compared to patient self‐report, and suggested training may improve accurate detection.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely documented that up to 49% of patients attending radiation therapy appointments may experience anxiety and distress . Anxiety is heightened during the first few visits to radiation oncology, particularly prior to starting treatment . During these visits, patients meet a variety of health care professionals (HCPs), including radiation oncologists (ROs), radiation therapists (RTs) and radiation oncology nurses (RONs).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety in patients with head and neck cancer receiving radiation therapy has been associated with treatment disruption 43 ; and data indicate that failure to complete head and neck cancer treatment in a timely manner is associated with decreased local control and survival. 44 Furthermore, patients with depression, anxiety, and/or neurocognitive dysfunction often fail to comply with treatment recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Many articles in the literature acknowledge this to be a significant problem, yet there is a paucity of research exploring methods to manage it. 22,23 Many articles in the literature acknowledge this to be a significant problem, yet there is a paucity of research exploring methods to manage it.…”
Section: Discussionmentioning
confidence: 99%